Studi Literatur: Analisis Pengendalian Internal Terhadap Sistem Informasi Akuntansi Penjualan dan Pendapatan pada PT. Malindo Feedmill Tbk - Anastasya Mechta Mediana; Herny Ria Mandag; Gabrielle Michaela; Dika Candra Laili; Tri Ratnawati (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Internal control is fundamental in the accounting system. Internal control (internal control) are policies and procedures that protect company assets and are presented accurately in accordance with applicable laws. Sales and revenue accounting information system is an information system that organizes a series of procedures and methods designed to generate, analyze, disseminate and obtain information to support decision making regarding sales and revenue. PT Malindo Feedmill Tbk is a multinational company engaged in production and sales, this company was founded in 1997 as a subsidiary branch of two Malaysian companies namely Leong Hup Holding Berhad and Emivest Berhad. The purpose of this study was to determine internal control related to sales and revenue accounting information systems at PT. Malindo Feedmill Tbk. The method used is descriptive analysis and secondary data from the company's website. The conclusion is the internal control itself at PT. Malindo Feedmill Tbk in sales has been good. However, it is possible that the management of biological assets is not good enough that there is a decrease in biological assets and their inventory.